A medical student's odyssey in 1990s Nigeria - Salim, Jamila; Abubakar, Ibrahim I (The Lancet (British edition), 2023)
Some autobiographies tell a factual individual story, allowing focus and continuity, whereas others bring in wider contextual and social factors to create a relatable story. Despite the cultural and temporal differences between Anya's story and our own perspectives—as a medical student and a clinical academic with responsibility for medical education in the UK today—there are many moments in this memoir that resonated with both of us, for instance, the anticipation in seeing your first cadaver, trying to figure out how to revise effectively for examinations, and the difficult experience of losing your first patient. By the end of the book, the reader is left wondering whether there will be a sequel that describes the next chapter in his life—specialist training, migration to the UK, or indeed the remarkable absence of a love interest through these formative years. Small by Small: Becoming a Doctor in 1990s Nigeria Ike Anya Sandstone Press, 2023 pp 304, £21·99, ISBN 9781914518096 JS is a second-year medical student at King's College London, UK.